The use of a stent-retriever to cause mechanical dilatation of a vasospasm secondary to iatrogenic subarachnoid haemorrhage. Issue 3 (June 2017) - Bhogal, Pervinder; Paraskevopoulos, Dimitris; Makalanda, Hegoda LD
Objective: To report the use of a stent-retriever in the management of vasospasm secondary to craniopharyngioma resection. Postoperative improvement was seen both clinically and on perfusion imaging. Methods: A patient was admitted for resection of a large craniopharygioma. On day 6 postoperatively the patient had an acute hemiparesis. A computed tomography angiogram and perfusion scan demonstrated acute right-sided cerebral vasospasm and a perfusion defect in the territory of the middle cerebral artery (MCA). Results: A pREset 4 × 20 mm stent-retriever was used to dilate the M1 and proximal M2 segments of the right MCA mechanically. This resulted in immediate dilatation of the spastic segment and improvement in the transit time on the angiogram. There was an improvement in the clinical status post-procedure and a computed tomography perfusion performed 24 hours after the procedure showed symmetrical perfusion. A computed tomography angiogram and magnetic resonance imaging performed 1 week later showed a symmetrical appearance to the MCA and no evidence of restricted diffusion. Conclusion: The use of commercially available stent-retrievers can cause mechanical dilatation of vasospastic vessels. The stents do not need to be deployed for a prolonged period nor do they need to be implanted to have a prolonged dilatory effect on the spastic vessels.